Assessment of Potential Geoheritage Sites, Promotion of Geotourism and Geoconservation of Kachchh District, India - Ganesh Muduli; Manisha Kumari; T Mahalakshmi (Geoconservation Research)
Investigation of new geoheritage sites, their conservation and promotion for tourism development have become a recent trend in the tourism sector. The Indian subcontinent exhibits a wide range of geological and geomorphological features, many with global significance. The Kachchh district of Gujarat is blessed with such geological and geomorphological elements, ranging in age from Mesozoic to Recent. This study describes some geologically rich sites and their potential to be ranked as geoheritage sites. To analyze the potential, we carried out four assessments: scientific value, educational value, touristic value, and the degradational risk. A total of 18 geodiversity sites have been considered for this assessment, all of them with unique significance. The authors appeal to the government of India for the conservation of these geodiversity sites through this paper, as we identify that all of them are at risk of degradation. We also provide some suggestions for the promotion of geotourism, some of which the government may adopt.